Acquired Methemoglobinemia Following Nitrobenzene Poisoning: An Unusual Case Report - Venkata Sarma Jayant Tetta; Tarun Kumar Suvvari; Sushmitha Reddy Sagili; Srinivasa Rajasekhar Kata; Sindhuja Karangula; Tejinder Singh; Vimal Thomas (Clinical Medicine Insights: Case Reports)
Methemoglobinemia is a rare but potentially life-threatening condition characterized by the oxidation of hemoglobin iron from ferrous (Fe²⁺) to ferric (Fe³⁺) state, impairing its oxygen-carrying capacity. Acquired forms can be triggered by exposure to oxidizing agents, such as nitrobenzene. We present the case of a 32-year-old female who developed symptomatic methemoglobinemia following oral ingestion of a commercial stimulant product containing nitrobenzene. She presented with peripheral cyanosis, breathlessness, and hypoxia unresponsive to oxygen therapy. A diagnosis of methemoglobinemia was confirmed, and prompt administration of intravenous methylene blue led to rapid clinical improvement. This case emphasizes the importance of early recognition of acquired methemoglobinemia in the context of toxic exposure, especially when conventional respiratory or cardiac pathology is excluded. Methylene blue remains the first-line antidote, offering effective and timely reversal of symptoms.